2018
DOI: 10.1039/c7pp00300e
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the photodynamic approach versus copper formulations in the control of Pseudomonas syringae pv. actinidiae in kiwi plants

Abstract: In the last decade, the worldwide production of kiwi fruit has been highly affected by Pseudomonas syringae pv. actinidiae (Psa), a phytopathogenic bacterium; this has led to severe economic losses that are seriously affecting the kiwi fruit trade. The available treatments for this disease are still scarce, with the most common involving frequently spraying the orchards with copper derivatives, in particular cuprous oxide (CuO). However, these copper formulations should be avoided due to their high toxicity; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Complete eradication of the biofilms with cationic porphyrins was achieved without visible leaf damage (Jesus et al . 2018) as opposed to what is observed with anionic porphyrins that can cause plant cell death (Leroy‐Lhez et al . 2019).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Complete eradication of the biofilms with cationic porphyrins was achieved without visible leaf damage (Jesus et al . 2018) as opposed to what is observed with anionic porphyrins that can cause plant cell death (Leroy‐Lhez et al . 2019).…”
Section: Resultsmentioning
confidence: 90%
“…actinidiae (Psa) with a cationic porphyrin produced an inactivation factor equivalent to that obtained in this work (6 log10) with half the concentration of a porphyrinic PS (50 µmol l −1 ) and a slightly higher light dose (Jesus et al . 2018). When a mixture of several porphyrin derivatives was used, the factor raised to 7·4 log10 with only 5·0 µmol l −1 of the PS mixture, and a light dose of 14 J cm −2 (Martins et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that natural photosensitizers such as coumarins and furocoumarins or synthetic ones such as phenothiazinium and porphyrins inactivated pathogenic agents as virus (Tobacco mosaic virus), bacteria ( Pseudomonas syringae ) and fungi ( Collectotrchum abscissum, Colletotrichum gloeosporioides, Collectotrichum acutatum, Aspergillus nidulans, Fusarium oxysporum, Fusarium moniliforme, Fusarium solani ) (Table 1 ). However, when spotted on orange tree and strawberry plants, or on kiwi contaminated leaves under solar radiation, the leaves and flowers were not affected by either natural/synthetic photosensitizers excepted for strawberry leaves that were damaged upon treatment with 100 μM phenothiazinium (Orlob, 1967 ; de Menezes et al, 2014a , b ; Fracarolli et al, 2016 ; Gonzales et al, 2017 ; Jesus et al, 2018 ). In another extended context, Issawi and co-workers conceived a double target strategy that could eradicate in the same time unwanted vegetation and plant pathogens without killing plants of agronomic interest (Figure 1B ).…”
Section: Direct Photodynamic Stress: An Old Story With Novel Developmmentioning
confidence: 99%
“…PSs are classi ed in many groups such as porphyrins, chlorins, coumarins, furocoumarins, phthalocyanines and phenothiaziniums. Porphyrins and chlorins such as chlorophyllin, have been shown to be very effective against bacteria on kiwi leaves tested in vitro (Jesus et al 2018;Glueck et al 2019). Coumarins, furocoumarin and phenothiazinium were shown to be active against the plant-infecting fungi Colletrichum acuratum and Aspergillus nidulans (De Menezes et al a, b;2014;Fracarolli et al 2016).…”
Section: Introductionmentioning
confidence: 99%